2015
DOI: 10.1167/iovs.15-18398
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Ambient Ozone on Unsaturated Tear Film Wax Esters

Abstract: Citation: Paananen RO, Rantamäki AH, Parshintsev J, Holopainen JM. The effect of ambient ozone on unsaturated tear film wax esters. Invest Ophthalmol Vis Sci. 2015;56:8054-8062. DOI:10.1167/iovs.15-18398 PURPOSE. Tear film lipid layer (TFLL) is constantly exposed to reactive ozone in the surrounding air, which may have detrimental effects on ocular health. Behenyl oleate (BO), a representative tear film wax ester, was used to study the reaction with ozone at the air-water interface.METHODS. Time-dependent … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 53 publications
0
11
0
Order By: Relevance
“…In a recent study evaluating the effects of exposure to ozone on the lipid component of tear film, the authors reported no signs of ozonolysis products in the tear fluid; this finding was most attributable to the antioxidant mechanisms in tear fluid and detoxification enzymes present in the cornea. [39,40]…”
Section: Discussionmentioning
confidence: 99%
“…In a recent study evaluating the effects of exposure to ozone on the lipid component of tear film, the authors reported no signs of ozonolysis products in the tear fluid; this finding was most attributable to the antioxidant mechanisms in tear fluid and detoxification enzymes present in the cornea. [39,40]…”
Section: Discussionmentioning
confidence: 99%
“…As shown recently, the surprisingly high (apparent) surface activity of meibum, 23 wax esters, 15,23 and OAHFAs 23 is very likely due to the rapid ozonolysis 19 of such lipids at the air-water interface. As expected based on their structure, such lipids show miniscule surface activity when the degradation of the lipids is prevented.…”
Section: Discussionmentioning
confidence: 68%
“…1). In contrast, when the ozonolysis of the lipids is not prevented, WEs degrade gradually into surfaceactive compounds 19 and show high surface activity. 15 Based on our preliminary studies, the same applies to CO (data not shown).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…An acrylic cover was put over the trough to protect the surface from dust and to suppress subphase evaporation. This enclosure was supplied with air passed through an Ozone Solutions ODS-3P ozone destruct unit (Hull, Iowa, USA) in order to prevent ozone-induced oxidation of the films (Paananen et al 2015). After 15 min, to allow chloroform evaporation, film area compression was started using two symmetrically moving barriers.…”
Section: Langmuir Surface Balance Experimentsmentioning
confidence: 99%